2022
DOI: 10.1038/s41598-022-24705-5
|View full text |Cite|
|
Sign up to set email alerts
|

Establishment of a finite element model of supination-external rotation ankle joint injury and its mechanical analysis

Abstract: By establishing a three-dimensional finite element model of ankle injury arising from supination and external rotation, the stress characteristics of the posterior malleolar surface can be obtained, and analysis of the corresponding stress on the lateral ankle can be conducted. Thin-layer computed tomography images of normal ankle joint in the supination and external rotation nonweight-bearing states was selected, to construct a three-dimensional data model of each ankle joint. A load was applied to examine di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…13 It is originally described that SER IV and PER IV are different from each other in terms of level of fractured fibula being low in SER and higher in PER. [1][2][3] Haraguchi et al found in their biomechanical study that low fibular fracture can be found in reproduced PER mechanism on cadavers. 18 this could explain the fracture in Case 4 since in the left side, the fibular fracture is low, while high on the contralateral side.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…13 It is originally described that SER IV and PER IV are different from each other in terms of level of fractured fibula being low in SER and higher in PER. [1][2][3] Haraguchi et al found in their biomechanical study that low fibular fracture can be found in reproduced PER mechanism on cadavers. 18 this could explain the fracture in Case 4 since in the left side, the fibular fracture is low, while high on the contralateral side.…”
Section: Discussionmentioning
confidence: 99%
“…Pronation external rotation or supination external rotation injuries are believed to be causing Maisonneuve fracture except that a classical Maisonneuve injury is a deltoid ligament injury with an associated syndesmotic and proximal fibular fracture. 2 Similarly, syndesmotic injury also known as high ankle sprain is known to be caused by External rotation moment of the dorsiflexed foot. 20 Dienstknecht et al reported a case in which a bilateral Maisonneuve fracture was sustained in an elderly patient by a low mechanism fall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations